Assessment Criteria of Effective teaching of Expert Teachers based on occupational health students’ viewpoints in Tehran University of Medical Sciences - Asghari, Mehdi; Rafieepour, Athena; Shahedi, Sara; Mirzahoseini, Marzieh; Chavooshi, Masoumeh; Abbassinia, Marzieh (Archives of Advances in Biosciences, 2016)
Notating the criteria of an expert teacher based on the students’ viewpoints and using them in teaching process has a prominent role in enhancing the education quality. This study aims at identifying those characteristics in occupational health students’ opinions. In this cross-sectional study in 2012, using random sampling method, 200 of occupational health students in Tehran University of Medical Sciences were selected. Requirement data collection was using a questionnaire with α= 0.85. The questions were designed in two domains, demographic and expert teacher criteria. Finally, data analysis was carried out through SPSS software version 16. Results showed that before, after and current education of four domains ability, features such as analysis method and text selection (81.4%), accurate and comprehensive examination in final (80.2%), dominance over the scientific subjects (91%) and in general, abilities, educational discipline and manual (86.4%) were respectively recognized as important factors for experted teacher. Moreover, no significant relationship was found among gender and field of study and the above mentioned four domains (p> 0/05). In this study, teaching ability was the most important factor in students’ viewpont; hence, it is recommended that the mentioned points should be taken inro more consideration in this domain for enhanced teachers’ operation.